Entrepreneurial Intention in Students of the Private Universities in Jakarta and Tangerang in the Era of Disruption - Meilani, Yohana F. Cahya Palupi; Canoy, Jr., Leonardo M. (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
Entrepreneurship is one aspect that influences the country's economic growth. Indonesia's entrepreneurship rate is still relatively low compared to other ASEAN countries, especially during the disruption period after the Covid 19 pandemic. The research aims to examine the influence of entrepreneurship education, family environment, and entrepreneurial motivation media on entrepreneurial intentions in students of the Faculty of Economics in Jakarta and Tangerang. This research method is quantitative, with a questionnaire to collect data from 160 students selected according to the criteria. The data was processed using the SEM Algorithm with the SmartPLS 4 application. The results showed that entrepreneurship education had a positive effect on entrepreneurial interest and motivation for entrepreneurship. Entrepreneurial motivation is able to mediate the positive influence of the family environment and entrepreneurship education on interest in entrepreneurship. The family environment has a positive influence on entrepreneurial motivation, while a negative influence on entrepreneurial interest. This research has important implications for educational institutions and the government to improve entrepreneurship education and a supportive environment for students who are interested in entrepreneurship in the era of disruption.